Knowledge of Chosen Family History and Depressive Symptoms in Sexual Minority Women - Gardella, Jamie M.; Parnes, McKenna F.; Hirst, William; Brown, Adam D. (Frontiers in Psychology, 2021)
Recent work on intergenerational memory has revealed a positive association between family of origin knowledge and wellbeing in adolescents. However, little is known about the generalizability of these data, as significantly less attention has focused on autobiographical memory sharing and wellbeing in historically marginalized communities. Given the high incidence of familial rejection and abandonment within the LGBTQIA+ community, close relationships with individuals outside of one’s family of origin, chosen families, often serve as an important source of social support. This study sought to examine the relationship between knowledge of a close non-family member and wellbeing among emerging adult sexual minority women (SMW) according to their gender presentation. A community sample from New York City comprised of heterosexual women (n= 50), masculine-presenting SMW (n= 50), and feminine presenting SMW (n= 50) completed measures associated with their knowledge of their family of origin, knowledge of a close non-family member, as well as self-reported measures of depression, emotion regulation, and socio-demographic questions. Family of origin knowledge was associated with lower levels of depression only among heterosexual women. However, heterosexual and SMW who knew more about their close non-family member reported lower levels of depression. Additionally, emotion regulation (cognitive reappraisals) mediated the relationship between knowing more about one’s chosen family and lower depressive symptom severity among heterosexual women, but this relationship was only significant for SMW who were at least moderately open about their sexuality. These findings extend the literature on the benefits of memory sharing to historically marginalized communities by showing that memory sources outside of one’s family of origin may be particularly important. Additionally, these data begin to shed light on potential mediating factors, such as emotion regulation and openness about one’s sexual identity, that underlie the links between memory sharing and metrics of wellbeing. Taken together, in contexts in which there may not be opportunities to learn about family history from one’s family of origin, it appears that access to stories from someone close outside of one’s family is also associated with lower levels of depression.